Strengthening Women's Trust in Social Capital in UIK - Rahel Widiawati Kimbal; Mister Gidion Maru (Journal of International Conference Proceedings (JICP), 2021)
This study aims to find forms of strengthening women's social capital trust in small industrial enterprises (UIK). Strengthening social capital trust should be an important capital in small industrial business activities involving women who are the pillars of the family economy. This study uses a qualitative research method through a case study at UIK Kacang tore. The data collection technique used triangulation in the form of observation, interviews and documentation. In the data analysis using the Spradley step-forward model. The results found in the field are various forms of strengthening social capital trust, which can be seen in: (1) Increasing self-confidence through increasing human resources (2) Maintaining honesty (3) Having high integrity (4) Loyalty (5) Firm and tenacious in decision making ( 6) build communication with the environment and (7) be responsible. The role of trust in social capital is a reinforcement for the progress of small industrial businesses to survive in the midst of the increasingly stringent onslaught of modern large business products. This is also a recommendation for Indonesian women to remain a mainstay for family economic resilience. Because women have a strong ideal capital resources.